Signatures of Dark Matter Burning in Nuclear Star Clusters - Lopes, Ilidio (2012)
In order to characterize how dark matter (DM) annihilation inside stars changes the aspect of a stellar cluster, we computed the evolution until the ignition of the He burning of stars from 0.7 M sun to 3.5 M sun within halos of DM with different characteristics. We found that, when a cluster is surrounded by a dense DM halo, the positions of the cluster' stars in the H-R diagram have a brighter and hotter turnoff point than in the classical scenario without DM, therefore giving the cluster a younger appearance. The high DM densities required to produce these effects are expected only in very specific locations, such as near the center of our Galaxy. In particular, if DM is formed by the 8 GeV weakly interacting massive particles recently invoked to reconcile the results from direct detection experiments, then this signature is predicted for halos of DM with a density ρχ = 3 × 105 GeV cm-3. A DM density gradient inside the stellar cluster would result in a broader main sequence, turnoff, and red giant branch regions. Moreover, we found that for very high DM halo densities the bottom of the isochrones in the H-R diagram rises to higher luminosities, leading to a characteristic signature on the stellar cluster. We argue that this signature could be used to indirectly probe the presence of DM particles in the location of a cluster.